Madrasah Principal Planning In Realizing The Quality Of Education At Madrasah Aliyah Yasti Sekura, Sambas Regency - Jeprianto; Amrah Kasim; Baharuddin; Putra, Purniadi (IJGIE (International Journal of Graduate of Islamic Education), 2025)
Madrasahs as Islamic educational institutions have a strategic role in improving the quality of education through effective planning. In Madrasah Aliyah YASTI Sekura, the planning of the madrasah principal is a crucial factor in determining the success of education, but there are still challenges in its implementation and evaluation. Studies related to the role of madrasah principals in education quality planning are still limited, so more in-depth research is needed to understand effective strategies in the madrasah context. This study uses a qualitative approach with interview, observation and documentation methods to reveal the planning process, the factors that influence it and its impact on the quality of education. The results show that the madrasah principal plays a strategic role in developing the vision, mission and goals of the madrasah through SWOT analysis as the first step of effective planning. Implementation that involves various parties and periodic evaluation of the programs implemented has proven to be able to significantly improve the quality of education. In addition, the success of this planning depends on the competence of the madrasah head in managerial aspects and optimal resource management. The implications of this study emphasize the importance of strengthening the competence of madrasah principals in strategic leadership aspects to create a sustainable education management model that can be applied in other madrasahs.